Effect of Omega-3 Deficiency and Positional Distribution of Docosahexaenoic Acid in Triacylglycerols on Tissue Lipids in Rats - Kulkarni, Amruta (fi=Turun yliopisto|en=University of Turku|, 2023)
Triacylglycerols (TAGs) are mostly chiral and they are metabolized in the chiral environment. They are not only a source of energy but also provide essential fatty acids (FAs). Long chain omega-3 polyunsaturated fatty acids [LC (n-3) PUFAs] are derivatives of essential FA α-linolenic acid. Dietary LC (n-3) PUFAs, especially docosahexaenoic acid (DHA), have been associated with normal retinal and neural development and prevention of cardiovascular and circulatory disorders among other biological effects. Various structures of lipids in food products can modulate the release and bioavailability of FAs during digestion and subsequent metabolic fate of FAs. The current knowledge of the bioavailability of these LC (n-3) PUFAs from different TAG structures lies on the fish oil to seal oil comparisons as LC (n-3) PUFAs, mainly EPA and DHA, are located predominantly in the sn-2 position in fish and squid oil, but in the sn-1 and sn-3 positions in seal oil. Despite of numerous biological functions of LC (n-3) PUFAs, very little is known about the absorption of DHA from the stereospecific forms of TAGs, especially from the enantiospecific TAGs. Before recent advances in the synthesis of enantiospecific structured TAGs, the investigation of the impact of dietary TAG structure on the absorption of FAs from sn-1 and sn-3 positions of TAGs has been limited. The aim of the current work was to investigate the effect of mild (n-3) deficiency and the effect of TAG structure on the extent of accumulation of DHA in organs, the bioavailability of DHA in plasma and feces, as well as on body weight, and organ weight. The effect of short-term first generation (n-3) deficiency was studied in a 33 day feeding trial on the lipid composition of different organs, plasma, and feces in rats. The effect of TAG structure on the FA content and composition of the different organs, plasma, and feces was investigated in a 5 day feeding trial with 360 mg/d enantiopure (> 96%) structured TAGs [sn-DHA-18:0-18:0 (sn-1 DHA) and sn-18:0-18:0-DHA (sn-3 DHA)] and their regioisomer [sn-18:0-DHA-18:0, sn-2 DHA). The lipids were extracted from organs, plasma, and feces, transformed into fatty acid methyl esters and analyzed by gas chromatography. The (n-3) deficiency resulted in lower DHA levels in the plasma, brain, testicle, visceral fat, heart, and lungs. The DHA level of the visceral fat of (n-3) deficient animals was 14% of the visceral fat of (n-3) adequately fed animals, being most affected by the (n-3) deficient diet feeding. The brain DHA was least affected with the DHA level of the (n-3) deficient animals being 86% of the (n-3) adequate animals. The DHA level of the organs was affected in the order of visceral fat > liver triacylglycerols > lung > heart > liver phospholipids > testis > eye > brain. The effect of feeding structured TAGs for 5 days following an (n-3) deficient diet resulted in less secretion of fecal DHA from the sn-2 position compared with the sn-1 and sn-3 positions suggesting superior absorption of DHA from the sn-2 position. A significantly higher level of DHA in the sn-1 DHA group compared to sn-3 DHA group in the liver TAG showed the difference in the absorption of DHA between the two primary positions of dietary TAG. The eye of the sn-1 DHA group led to a small but insignificant increase in DHA level compared to the sn-3 DHA group and stearic acid (18:0, STA) in liver PLs was found to be significantly higher sn-1 DHA group as compared to the sn-3 DHA group. This indicated a possible difference in the absorption of FAs from sn-1 and sn-3 positions of TAG. This work provides the information to evaluate the conditions needed to reach mild (n-3) deficiency in the first generation of rats and to evaluate the feasibility to collect data from a variety of organs. Also, the short term feeding of structured TAGs provides evidence on the possible differences in the absorption of DHA from the primary positions (sn-1 and sn-3) of TAG in the liver TAG fraction. Together, this work shed light on the influence of the positional distribution of DHA in dietary TAGs on plasma, fecal, and organ lipids and (n-3) deficiency on the bioavailability of DHA strengthening the current understanding of lipid biochemistry.

Triasyyliglyserolit (TAG) ovat enimmäkseen kiraalisia ja niiden aineenvaihdunta tapahtuu kiraalisessa ympäristössä. Ne eivät ole vain energialähde, vaan ne sisältävät myös välttämättömiä rasvahappoja. Pitkäketjuiset monityydyttymättömät omega-3 rasvahapot [LC (n-3) PUFA:t] ovat välttämättömän α-linoleenihapon johdannaisia. Ruokavalion LC (n-3) PUFA:t, erityisesti dokosaheksaeenihappo (DHA), on yhdistetty verkkokalvon ja hermoston normaaliin kehitykseen sekä sydän- ja verisuonisairauksien sekä verenkiertohäiriöiden ehkäisyyn, muiden biologisten vaikutusten ohella. Elintarvikkeiden erilaiset lipidirakenteet voivat vaikuttaa rasvahappojen vapautumiseen ja biosaatavuuteen ruoansulatuksen aikana sekä niiden myöhempään aineenvaihduntaan. Nykyinen tieto LC (n-3) PUFA:ien biosaatavuudesta eri TAGrakenteista perustuu kalaöljyn ja hyljeöljyn vertailuun, koska eikosapentaeenihappo (EPA) ja DHA sijaitsevat pääasiassa sn-2 -asemassa kala- ja kalmariöljyssä, mutta sn-1 ja sn-3 -asemissa hyljeöljyssä. Pitkäketjuisten (n-3) rasvahappojen lukuisista biologisista toiminnoista huolimatta on hyvin vähän tietoa siitä, miten DHA:n tarkka sitoutumiskohta (sn-1, sn-2, sn-3) TAG-molekyylissä vaikuttaa imeytymiseen. Ennen viimeaikaista edistystä enantiospesifisten strukturoitujen TAG:ien synteesissä, ravinnon TAG-rakenteen vkutusta rasvahappojen imeytymiseen TAG:ien sn-1- ja sn-3-asemista on tutkittu hyvin vähän. Tämän väitöskirjatyön tavoitteena oli tutkia, miten lievä (n-3) rasvahappojen puute ja TAG-rakenne vaikuttavat DHA:n kerääntymiseen eri elimiin, DHA:n biosaatavuuteen määrittämällä plasman ja ulosteen DHA-pitoisuudet, sekä koe-eläimen ja sen elinten painoon. Väitöskirjatyön 33 päivää kestäneessä ruokintakokeessa tutkittiin lyhytaikaisen, ensimmäisen sukupolven (n-3) rasvahappojen puutteen vaikutusta rottien eri elinten, plasman ja ulosteiden lipidikoostumukseen. TAG-rakenteen vaikutusta eri elinten, plasman ja ulosteiden rasvahappopitoisuuteen ja -koostumukseen tarkasteltiin viisi päivää kestäneessä ruokintakokeessa, jossa 360 mg enantiopuhtaita (> 96 %) TAG-isomeereja [stereoisomeerit sn-DHA-18:0-18:0 (sn-1 DHA) ja sn-18:0-18:0-DHA (sn-3 DHA), niiden regioisomeeri sn-18:0-DHA-18:0, sn-2 DHA] sisällytettiin rottien ruokavalioon päivittäin (n-3) rasvappojen puutetta aiheuttavan jakson jälkeen. Lipidit uutettiin elimistä, plasmasta ja ulosteista. Rasvahapot muunnettiin niiden metyyliestereiksi ja analysoitiin kaasukromatografialla. (n-3) puutos johti alhaisempiin DHA-tasoihin plasmassa, aivoissa, kiveksissä, sisäelimiä ympäröivässä rasvassa, sydämessä ja keuhkoissa. (n-3) puutoksessa eläinten sisäelinten ympärillä olevan rasvan DHA-taso laski eniten verrattuna riittävästi ruokittujen eläinten sisäelinten rasvan DHA-tasoon ollen siitä vain 14 %. Tutkituista elimistä vähiten vaikutusta ruokinnalla oli aivojen DHA:n määrään. (n-3) puutoksessa aivojen DHA-taso oli 86 % (n-3) rasvahappoja riittävästi saaneiden koe-eläinten aivojen DHA-tasosta. Elinten DHA-tasoon (n-3) rasvahappoja puutteellisesti sisältänyt ruokinta vaikutti seuraavassa järjestyksessä: sisäelimiä ympäröivä rasva > maksan triasyyliglyserolit > keuhkot > sydän > maksan fosfolipidit > kivekset > silmät > aivot. Kun (n-3) puutteellisen ruokavalion jälkeen strukturoituja TAG:eja sisällytettiin ruokavalioon 5 päivän ajan, DHA:ta erittyi vähemmän ulosteeseen ruokavalion DHA:n sijaitessa sn-2-asemassa verrattuna sn-1- ja sn-3-asemiin, mikä viittaa DHA:n parempaan imeytymiseen sn-2-asemasta. Merkittävästi korkeammat DHA-tasot maksan TAG:eissa sn-1-DHA-ryhmässä verrattuna sn-3-DHAryhmään osoittivat eron DHA:n imeytymisessä ravinnon TAG:n kahden primaarisen aseman välillä. Tutkimuksessa havaittiin, että sn-1 DHA-ryhmän silmien DHA-pitoisuus oli vähän, mutta ei merkittävästi suurempi verrattuna sn-3 DHA-ryhmään. Lisäksi havaittiin, että steariinihapon määrä maksan fosfolipideissä oli merkitsevästi korkeampi sn-1 DHA-ryhmässä verrattuna sn-3 DHA-ryhmään. Tämä viittaa mahdolliseen eroon rasvahappojen imeytymisessä TAG:n sn-1- ja sn-3-asemista. Väitöskirjatyö antaa tieteellistä tietoa arvioitaessa olosuhteita lievän (n-3) puutteen saavuttamiseksi ensimmäisessä rottasukupolvessa sekä auttaa tulevia tutkimuksia pohdittaessa datan keräämistä useista eri elimistä. Väitöskirjatutkimus TAG-rakenteen vaikutuksesta DHA:n biosaatavuuteen tarjoaa todisteita siitä, että DHA:n imeytymisen erot TAG:n primaarisista asemista (sn-1 ja sn-3) näkyvät eroina maksan TAG:ssa. Yhteenvetona tämä työ tarjosi tieteellistä tietoa ravinnon TAG:en DHA:n paikkajakauman vaikutuksesta plasman, ulosteiden ja elinten lipideihin sekä (n-3) puutoksen vaikutuksesta DHA:n biosaatavuuteen vahvistaen nykyistä ymmärrystä lipidien biokemiasta.